Pengaruh Pengembangan Kompetensi Teknis, Customer Relationship Management, dan Kualitas Sistem Prosedural terhadap Keunggulan Bersaing pada Perusahaan PT Spectrum Lintas Service Batam - Safa Hisham Kabbani; Mefri Yudi Wisra; Suyono Suyono (Lembaga Pengembangan Kinerja Dosen, 2026)
Analysis of the business situation experienced by PT Spectrum Lintas Service indicates that the achievement of success in obtaining large-scale project contracts is greatly influenced by the technical image and confidence given by clients. This study aims to investigate the impact of Improving Technical Qualifications, Customer Relationship Management, and Procedural Governance Quality on the Achievement of Competitive Advantage at PT Spectrum Lintas Service. The study population consisted of a total of 141 customers. The data analysis approach used was the SPSS tool to test the research hypothesis through t-test and F-test. The results of the F-test showed a significance probability value of 0.000 smaller than 0.05. Based on the findings, it can be concluded that improving technical qualifications, customer relationship management, and procedural governance quality significantly contribute to the competitive advantage of PT. Spectrum Lintas Service. Improving technical qualifications has a negative but not substantial impact on competitive advantage, with a significance value of 0.110 greater than 0.05. Customer relationship management has an impact on competitive advantage with a significance value of 0.00, which is smaller than 0.05. The quality of the procedural system has a significant influence on competitive advantage.